2018
DOI: 10.1111/sms.13053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute isometric resistance exercise on cervicomedullary motor evoked potentials

Abstract: Cervicomedullary motor evoked potentials (CMEPs) in relaxed biceps brachii have been reported to facilitate after acute isometric exercise of the elbow flexors. This facilitation, which reflects either enhanced corticospinal transmission or increased motoneurone excitability, has only been documented in the limb posture used during exercise. In Experiment 1, we tested if these spinal changes "transfer" to a second posture. Fourteen individuals completed 12 sets of high-force isometric contractions of the elbow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous studies showed that ST intensity affected CSE but not spinal excitability measured by cervicomedullary electrical stimulation . Furthermore, increases in corticospinal transmission and/or α‐motoneuron excitability after acute ST are not always present . For that reason, mechanisms other than spinal changes were proposed to explain the increases in CSE after acute ST. Increases in corticospinal neuron excitability or reductions in the efficacy of the intracortical inhibitory circuits can both increase the efficacy of the excitatory input to α‐motoneurons thereby increasing the response to TMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that ST intensity affected CSE but not spinal excitability measured by cervicomedullary electrical stimulation . Furthermore, increases in corticospinal transmission and/or α‐motoneuron excitability after acute ST are not always present . For that reason, mechanisms other than spinal changes were proposed to explain the increases in CSE after acute ST. Increases in corticospinal neuron excitability or reductions in the efficacy of the intracortical inhibitory circuits can both increase the efficacy of the excitatory input to α‐motoneurons thereby increasing the response to TMS.…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, increases in corticospinal transmission and/or α-motoneuron excitability after acute ST are not always present. 26 For that reason, mechanisms other than spinal changes were proposed to explain the increases in CSE after acute ST. Increases in corticospinal neuron excitability or reductions in the efficacy of the intracortical inhibitory circuits can both increase the efficacy of the excitatory input to α-motoneurons thereby increasing the response to TMS. However, we found no reductions in GABAa or GABAb receptor-mediated cortical inhibition.…”
Section: Trained Sidementioning
confidence: 99%
“…Several studies have demonstrated transient increased MEPs as an immediate result of post-exercise facilitation in ablebodied participants after a short period of repetitive contraction exercise in thenar 57 , wrist 58 , forearm 59 , or leg muscles 60,61 .…”
Section: Study Sessionmentioning
confidence: 99%
“…Participants will be asked again at the first minute of the following deflation period to check if the pain, discomfort, or other symptoms persist. Several studies have demonstrated transient increased MEPs as an immediate result of post-exercise facilitation in able-bodied participants after a short period of repetitive contraction exercise in thenar 58 , wrist 59 , forearm 60 , or leg muscles 61,62 .…”
Section: Screening Sessionmentioning
confidence: 99%